2015
DOI: 10.1371/journal.pone.0124210
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship and Mode of Action of a Frog Secreted Antibacterial Peptide B1CTcu5 Using Synthetically and Modularly Modified or Deleted (SMMD) Peptides

Abstract: All life forms are equipped with rapidly acting, evolutionally conserved components of an innate immune defense system that consists of a group of unique and diverse molecules known as host defense peptides (HDPs). A Systematic and Modular Modification and Deletion (SMMD) approach was followed to analyse the structural requirement of B1CTcu5, a brevinin antibacterial peptide amide identified from the skin secretion of frog Clinotarsus curtipes, India, to show antibacterial activity and to explore the active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
6
26
0
Order By: Relevance
“…Strong inhibitory activity against MRSA and VRE may be a proof of the competence of HDPs against the multidrug‐resistant pathogens. These observations were in good agreement with the earlier studies on the peptides identified from Clinotarsus curtipes , Rana rugosa , and Glandirana emeljanovi …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Strong inhibitory activity against MRSA and VRE may be a proof of the competence of HDPs against the multidrug‐resistant pathogens. These observations were in good agreement with the earlier studies on the peptides identified from Clinotarsus curtipes , Rana rugosa , and Glandirana emeljanovi …”
Section: Discussionsupporting
confidence: 93%
“…It was previously reported that C‐terminal amidation increases peptide activity and increases its hemolytic effect, which is inconsistent with our results. These peptides exhibit hemolytic activity similar to amidated brevinin1 isolated from C. curtipes , another endemic frog species of Western Ghats, where the percentage hemolysis is below 40% . Results of MTT assay (Figure ) revealed that both amidated and acidic brevinin1 peptides were highly toxic to the Hep 3B cancer cell line and less toxic to normal HEK cells (similar to the positive control, silymarin, a potential anticancer drug).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This similarity of AMPs derived from different species indicates that they are likely to have an evolutionary origin, the significance of this characteristic structure on potency of AMPs against microbes remains to be elucidated, though. Previous paper reported that deletion of “Rana box” radically abolished the antimicrobial activity of AMP, while others dismissed its function, as the elimination or replacement of cysteine residue did not affect potency of AMPs (Kwon et al, 1998; Vignal et al, 1998; Abraham et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, study on brevinin 1E amide suggested that the disulphide bridge was pivotal for the α-helical structure but not significant for its antimicrobial potency, as activity was unaffected even when cysteine residues are substituted by serine (Kwon et al, 1998). In contrast, the elimination of the heptapeptide motif in B1CTcu5, an AMP isolated from Clinotarsus curtipes , prominently reduced antibiotic and hemolytic activity of it (Abraham et al, 2015). Nigrocin is a representative anuran AMP family, and after sequence alignment between nigrocin-HL and other members of nigrocin family reported previously, a highly conserved heptapeptide motif “CGLXGLC” named “Rana box” at C-terminus was confirmed in the nigrocin family (Park et al, 2001; Conlon et al, 2006; Li et al, 2007; Che et al, 2008; Iwakoshi-Ukena et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%